To Suffragettes. A Word of Advice…’. Blast, Gender and ‘Art under Attack’ - Macedo, Ana Gabriela (Cadernos de Literatura Comparada, 2014)
“Art under Attack” is the title of an exhibition that took place at Tate Britain in London (Oct. 2013-Jan. 2014). In this paper I will concentrate on an exemplary case of such an iconoclastic attack, which was indexed in this exhibition as political – I am referring to the attack of the suffragette Mary Richardson to Velázquez’s Rokeby Venus, in March 1914. My argument is that militant Suffragettes were in fact the first Guerilla Girls of the 20th century, largely anticipating the latter performative and anti-establishment gesture in the Museum and denouncing the institutional space of art as deeply gendered and discriminatory, and, moreover, reclaiming it as a public space of political citizenship, democratic intervention and anti-iconoclastic debate. This will be discussed in the context of and in a dialogue with the Vorticist aesthetics and the outbreak of World War I. In fact Blast 1, the shocking bright pink Vorticist magazine was published on the 20th June 1914, exactly three months after the Rokeby Venus’ attack, and roughly a month (exactly 33 days), before the first World War was declared through the invasion of Serbia (28 July 2014).